Predicting school innovation The role of collective efficacy and academic press mediated by faculty trust - Schwabsky, Nitza; Erdogan, Ufuk; Tschannen-Moran, Megan (Emerald Group Publishing Ltd, 2020)
Purpose The purpose of this paper is to examine the role of collective teacher efficacy, academic press and faculty trust, all of which are components of academic optimism (AO), in predicting school innovation. In addition, the authors explored the extent to which faculty trust mediates the association between collective teacher efficacy and academic press with school innovation. Design/methodology/approach In all, 1,009 teachers from 79 schools in Northern Israel completed anonymous questionnaires about AO and innovation. Aggregation, descriptive statistics, bivariate correlation analyses and mediation analysis were performed to analyze the data. Findings Results showed that the components of AO, i.e., collective teacher efficacy, academic press and trust, were positively correlated to school innovation, and that trust mediated the relationship between collective teacher efficacy and school innovation. The study results confirmed that AO holds a significant predictive value in school innovation and highlights the importance of trust in supporting innovation. Originality/value This is the first study to examine the role of the components of AO in predicting innovation. By using a robust sample, the authors were able to examine the proposed school-level model with respect to the factors that affect school innovation. Originality also lies in the organizational approach to educational innovation in relation to faculty's beliefs and behaviors.
Keywords: Academic optimism; Academic press; Collective teacher efficacy; School innovation; Teachers' trust